2021
DOI: 10.3389/fnmol.2021.765181
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Channel 4 Small-Molecule Inhibition Alleviates Migraine-Like Behavior in Mice

Abstract: Migraine is a common neurological disorder with few available treatment options. Recently, we have demonstrated the role of transient receptor potential cation channel subfamily C member 4 (TRPC4) in itch and the modulation of the calcitonin gene-related peptide (CGRP), a biomarker and emerging therapeutic target for migraine. In this study, we characterized the role of TRPC4 in pain and evaluated its inhibition as anti-migraine pain therapy in preclinical mouse models. First, we found that TRPC4 is highly exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…A recent study showed that TRPC4 is highly expressed in TG neurons and that pharmacological inhibition of TRPC4 significantly prevented migraine-linked cutaneous mechanical hypersensitivity and increased plasma levels of CGRP [133]. Specifically, we found that TRPC4 is highly expressed in TG tissues and neurons, with most of these neurons also expressing CGRP and innervating the skin.…”
Section: Trpc4 Channel As An Emerging Target For Antimigraine Drugssupporting
confidence: 54%
See 2 more Smart Citations
“…A recent study showed that TRPC4 is highly expressed in TG neurons and that pharmacological inhibition of TRPC4 significantly prevented migraine-linked cutaneous mechanical hypersensitivity and increased plasma levels of CGRP [133]. Specifically, we found that TRPC4 is highly expressed in TG tissues and neurons, with most of these neurons also expressing CGRP and innervating the skin.…”
Section: Trpc4 Channel As An Emerging Target For Antimigraine Drugssupporting
confidence: 54%
“…↓ mechanical allodynia; ↓ CGRP plasma levels [133] TRPV1, the first of many thermosensitive TRP channels to be identified, functions as a noxious heat sensor that is activated by temperatures greater than 42°C and pH changes [65,66]. Additionally, it is triggered by exogenous stimulants, such as capsaicin from chili peppers, and endogenous stimulants, such as anandamide produced in inflammatory processes [65][66][67].…”
Section: Trpm8mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, high plasmatic levels of CGRP have already been demonstrated in external jugular venous blood, saliva, and cerebrospinal fluid of migraine patients during an attack [3]. Besides, migraine animal model induce an increase in circulating CGRP levels in plasma [13,49], cerebrospinal fluid of the nestin/hRAMP1 transgenic mice [45]. Additionally, CGRP may trigger the release of pro-inflammatory cytokines [44], particularly IL-6 and TNF-α, which are also increased in the plasm of migraine patients [14,56].…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, in rodents, pro-inflammatory cytokines were described as inductors of primary afferent nociceptors sensitization ( Khasar et al, 2008 ; Kursun et al, 2021 ) and high CGRP plasma levels have already been demonstrated in external jugular venous blood, saliva, and cerebrospinal fluid of migraine patients during an attack ( Alpuente et al, 2020 ). The migraine animal model also induces an increase in circulating CGRP levels in plasma ( Cohen et al, 2021 ; Sun et al, 2021 ) and cerebrospinal fluid of the nestin/hRAMP1 transgenic mice ( Recober et al, 2009 ). Additionally, CGRP may trigger the release of pro-inflammatory cytokines ( Ray et al, 2021 ), particularly IL-6 and TNF-α, which are also increased in the plasm of migraine patients ( Yücel et al, 2016 ; Conti et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%